Optimal TCSC Allocation via Chaotic Immune Symbiotic Organisms Search for Voltage Profile Improvement - Mohamad Zamani M.K.; Musirin I.; Suliman S.I.; Syed Mustaffa S.A.; Mohd Ali N.Z.; Mansor M.H.; Abdul Hamid Z. (EDP Sciences, 2023)
Computer programming; Flexible AC transmission systems; Thorium compounds; Allocation problems; Flexible ac transmission system (FACTS); Optimal allocation problems; Optimal compensations; Optimization techniques; Power system operators; Thyristor controlled series compensator; Voltage profile improvement; Particle swarm optimization (PSO)